Efektivitas Fungsi Inspektorat dalam Pengawasan Keuangan Daerah di Kota Gorontalo - Yulianty Ibrahim; Andi Mardiana; Syawaluddin Syawaluddin (Al-Buhuts, 2021)
The local government is the executive that is entrust with the management of regional finances, which financial management must be transparent, easy to understand by the community, can be accept by the community as executor or manager and must be undergone an audit. In the accordance of these issues, we need a supervision that is carry out both external and internal supervision. A supervisor should be an institution or person from an organizational unit other than the audited organizational unit, while internal supervision is carry out by an institution or a person within the audited organizational unit carries out external supervision. Supervision is an activity to obtain certainty whether the implementation of work or activities has been carry out in accordance with the original plan. Monitoring activities are comparing existing conditions with what should have happened. The supervision of the inspectorate of Gorontalo City has the function of reviewing the financial reports of local governments as well as to help agencies to carry out their duties better. In order for this supervision to run smoothly in accordance with the stated objectives, it is necessary to have the role of technical and functional institutions related to supervisory duties both in the region and at the central effectively. If irregularities or obstacles are found, it is hoped that they can be controlled immediately, and corrective action can be taken immediately. Through this corrective action, it is hoped that the implementation of the activities concerned can still achieve its objectives maximally to improve the work unit's performance.